Menimbang Kecerdasan Emosional dalam Mengatasi Degradasi Moral - Asmarita, Desi (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
Emotional intelligence as a gift from God. Emotions require proper control from an early age in order to develop well. The large number of cases related to the decline in morals among students requires the instilling of the concept of emotional control in students. The purpose of this article is to examine and discuss emotional intelligence from the perspective of the Koran as an effort to overcome moral degradation among students. This research uses the library research method by utilizing data sources in the form of library literature such as articles, journals and websites that discuss emotional intelligence from the perspective of the Al-Qur'an. The data analysis technique used is descriptive analysis. The results of this research are that humans are described in the Al-Qur'an as God's creation and are given extraordinary potential in the form of emotions that will have an impact on life. The ability to control emotions, that is what is called emotional intelligence. The characteristics of emotional intelligence can be identified from self-awareness, self-regulation abilities, motivation, empathy and social skills. All of these characteristics of emotional intelligence were described in the Qur'an long before Western theory used the term for emotional intelligence. Emotional intelligence in the Qur'an is exemplified by being patient, fearing Allah, holding back anger, controlling sadness and happiness as best as possible in accordance with instructions from Allah in the Qur'an. The conclusion from this research is that controlling emotions is not an easy thing when it is not based on faith in the guidelines of the Al-Qur'an. This control needs to be trained from an early age through role model education from parents to their children.Keywords: Al-Qur'an; Emotional Intelligence; Neuroscience; Moral; Learner.